DEVELOPMENT AND VALIDATION OF UV-SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF GEMCITABINE HYDROCHLORIDE IN BULK AND POLYMERIC NANOPARTICLES - Kaur, Taranjit; Kaur, Sukhjinder; Kaur, Parminderjit (International Journal of Applied Pharmaceutics, 2017)
Objective: The objective of the present work was to develop and validate a novel, specific, precise and reliable method for estimation of gemcitabine hydrochloride in bulk and polymeric nanoparticles using UV-visible spectroscopy method. Methods: The UV-Visible spectrophotometric determination was performed with double beam Systronics UV-visible spectrophotometer; model UV-2201 (India). The proposed methods were validated for various parameters like linearity, precision, accuracy, robustness, ruggedness, detection, quantification limits, and formulation analysis as per international conference on harmonization (ICH) guidelines. Results: The method was based on measurement of absorbance at wavelength maxima i.e. 267.2 nm, Î»max of the drug in distilled water, phosphate buffer pH 6.8 and 7.4. The method obeyed Beer Lambert's law in the concentration range of 5-30 Âµg/ml andR2-value was found to be 0.999. Moreover, the % drug recovered from polymeric nanoparticles was found to be 97.97%. Conclusion: According to results, the currently developed method shows compliance with acceptance criteria with Q2 (R1) and international conference on harmonization (2005) guidelines, because the % RSD was found to be less than 2%. The developed method was simple, accurate and prÃ©cised.